1967
DOI: 10.1136/gut.8.3.230
|View full text |Cite
|
Sign up to set email alerts
|

An analysis of the autonomic control of gastrointestinal motility in the cat.

Abstract: EDITORIAL COMMENT These observations in the cat show that the stomach has a high level of extrinsic, and a low level of intrinsic, cholinergic control, but this is reversed in the small intestine. Similar studies are clearly needed in man to provide us with logical tests for the management of motility disorders.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3

Citation Types

2
11
0
1

Year Published

1971
1971
1992
1992

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 37 publications
(14 citation statements)
references
References 41 publications
2
11
0
1
Order By: Relevance
“…This finding is in agreement with previous reports which outlined the existence of intestin al movements early in the postoperative period with various techniques: balloon kymography [19,20,22], radiological methods [16,18,21] or study of abdominal sounds [1,6,25,27]. Therefore, it may be suggest ed that the 'physiological' ileus is not due to the disappearance of intes tinal mechanical activities but to their disorganization.…”
Section: Discussionsupporting
confidence: 82%
“…This finding is in agreement with previous reports which outlined the existence of intestin al movements early in the postoperative period with various techniques: balloon kymography [19,20,22], radiological methods [16,18,21] or study of abdominal sounds [1,6,25,27]. Therefore, it may be suggest ed that the 'physiological' ileus is not due to the disappearance of intes tinal mechanical activities but to their disorganization.…”
Section: Discussionsupporting
confidence: 82%
“…These findings have been confirmed repeatedly (Nachlas, Younis, Roda, and Wityk, 1972;Neely, 1968). Most of these studies have been radiological observations of barium in the gastrointestinal tract, and, althoughthestudies have been primarily directed at the stomach, most workers have observed that barium is also held up in the colon.…”
mentioning
confidence: 60%
“…It has been shown in experimental animals that the activity of the small intestine returns to normal within a few hours following surgery (Tinckler, 1965;Baker and Webster, 1968). Early return of activity has also been shown in man using a radiotelemetering capsule (Ross, Watson, and Kay, 1963 (Nachlas, Younis, Roda, and Wityk, 1972;Neely, 1968). Most of these studies have been radiological observations of barium in the gastrointestinal tract, and, althoughthestudies have been primarily directed at the stomach, most workers have observed that barium is also held up in the colon.…”
mentioning
confidence: 99%
“…The mode of action of glucagon differs from other mediators of colonic relaxation. For instance, atropine acts by competitive blockade at postganglionic parasympathetic junctions and is known to inhibit colonic motility in vitro (Neely and Catchpole, 1967) and in vivo (Misiewicz, 1974). However, in doing so, it preserves the regular slow wave activity and has no effect on either its frequency, amplitude, or incidence (Taylor, 1974).…”
Section: Discussionmentioning
confidence: 99%
“…Using a cat colon model in situ, Neely and Catchpole (1967) showed that sympathetic inhibition was mediated mainly through P receptors.…”
Section: Discussionmentioning
confidence: 99%